Pre- and post-transformation changes in two mulberry varieties for semi-sweet wine production - Yinyin Lian; Yingmei Meng; Mei Wang; Jiajia Song; Huayi Suo; Yu Zhang (Food Chemistry: X, 2025)
Mulberries, despite its rich nutritional and health-promoting properties, are commonly associated with high post-harvest waste. Fermenting them into mulberry wine can increase their added value. This study investigated changes in mulberry physicochemical properties, antioxidant capacity, volatile, and non-volatile compounds pre- and post- fermentation using two varieties (Seedless Dashi and Taiwanese long-fruited mulberries). Fermentation significantly increased titratable acidity and antioxidant capacity, while reducing soluble solids, total sugars, ascorbic acids, and oxalic acids. Post-fermentation analysis showed a significant increase in tartaric acid, malic acid, and newly formed succinic acid, with total amino acids decreasing. A comprehensive analysis identified 67 volatile flavor compounds pre- and post-fermentation. A total of 28 among them (odor activity value >1) contributed to aroma. Orthogonal partial least squares discriminant analysis (OPLS-DA) identified 13 key markers distinguishing pre- and post-fermentation samples. These findings provide insights for optimizing mulberry wine production and industrial applications.